Evaluation of emotional divorce prediction based on sexual issues of couples - Golmohammadi , Hamed; Alimardani , Mohammad (Journal of Assessment and Research in Applied Counseling (JARAC), 2022)
Background and Aim: The aim of this study was to predict emotional divorce based on sexual satisfaction among couples undergoing couples therapy in Tehran. Methods: The method of this descriptive-analytical study was correlational. The statistical population included all couples who referred to two counseling centers for psychology and family therapy in Tehran in 1398, from which 120 couples were selected by available methods and answered the Multi-Questionnaire of Sexual Issues (MSQ) and Emotional Divorce. They gave. Results: The data were analyzed by stepwise regression method using SPSS software version 26. Statistical findings and results of regression analysis test showed that out of twelve subscales of sexual problems of spouses that were related to their emotional divorce, six subscales had a significant effect. Conclusion: According to the research findings, it can be concluded that when sexual satisfaction and sexual awareness of spouses are reduced and sexual mental employment, internal sexual control, sexual control and motivation The more sexual, the more likely they are to have an emotional divorce.